Initial experience with a homemade “hybrid-tome” for needle-knife precut in patients with difficult biliary cannulation - De la Morena Madrigal, Emilio J.; Rodríguez García, Isabel; Galera Ródenas, Ana Belén; Pérez Arellano, Elena (Endoscopy International Open, 2021)
Background and study aims Current clinical guidelines recommend needle-knife precut (NKP) as the primary and best method for performing a biliary cannulation (BC) when simple techniques fail and the criteria are met for difficult BC (DBC). However, many endoscopists avoid or defer early NKP in favor of alternative, simpler techniques that have not been shown to be either safer or more effective. Our goal is to test a device that provides the needle-knife papillotome (NKPT) with traction capability and which can facilitate the learning and execution of NKP.Patients and methods This was a descriptive bicentric observational study of a personal cohort of patients undergoing early NKP to analyse the efficacy and safety of the technique with a “hybrid-tome” (HT) built using the isolated core of a NKPT and a conventional canulotome.Results Over a 4-year period, we performed 43 NKPs with the HT, achieving BC in one or two steps in all cases. The 100 % technical success was matched by a 95 % clinical success rate. We recorded 11 adverse events (23 %): five hemorrhages, four pancreatitis, and two cholangitis. In addition to the objective data, we confirmed that HT facilitates alignment with the duodenal papilla and the execution of pre-cutting, especially if the papilla is intradiverticular or hidden by folds.Conclusions The HT tested seems to help trained endoscopists to perform NKP, especially in some anatomic situations, which can improve compliance with the guidelines recommended for early NKP in patients with DBC.